Beyond zero deforestation in the Brazilian Amazon Progress and remaining challenges to sustainable cattle intensification - Pacheco, Pablo; Piketty, Marie-Gabrielle; Poccard-Chapuis, Rene; García Drigo, Isabel; El Husny, Jamil Chaar; Gomes, Mario; Tourrand, Jean François (Center for International Forestry Research, 2017)
Key Messages • A governance approach, combining public policy and private initiatives was effective in slowing down deforestation, but was unable to support a transition to more sustainable production systems. • New technical intensification models must be identified for low-productivity systems in degraded lands, adapted to the biophysical and sociotechnical conditions of the Amazonian landscapes. • Multiple constraints inhibit progress toward sustainable intensification of cattle ranching, and reversing them requires that all such constraints be addressed in a coordinated way. • Designing options that work for all stakeholders, and monitoring and verifying progress of territories toward sustainability is essential to support current public policies and private initiatives.